Науково обґрунтована концепція контролювання ентомофітопатогенного комплексу у посівах пшениці озимої північного степу України - Матюха, Володимир Леонідович; Matyukha, V. L. (Дніпровський ДАЕУ, 2024)
У дисертації здійснено теоретичне узагальнення та представлено нове теоретичне обґрунтування й вирішення наукової проблеми захисту пшениці озимої від бур’янів, хвороб та шкідників у Північному Степу України, на базі чого розроблено ефективні бакові суміші гербіцидів, інсектогербіцидів та інсектофунгіцидів. У дисертаційній роботі наведено результати дослідження з оцінювання технічної, економічної та енергетичної ефективності бакових сумішей препаратів. Уперше розроблено: науково обґрунтовану концепцію боротьби проти ентомофітопатогенного комплексу в посівах пшениці озимої після непарових попередників на чорноземах звичайних Північного Степу України; положення щодо оптичної щільності агрофітоценозів пшениці озимої м’якої, вирощуваної після непарових попередників, з урахуванням економічного порогу шкодочинності бур'янів; бакові суміші гербіцидів, інсектицидів та фунгіцидів, що можуть у поєднаннях між собою ефективно знищувати цілий комплекс захворювань, шкідників і різні біогрупи бур’янових рослин (зокрема, злісних коренепаросткових багаторічників та карантинних бур’янів-алергенів), без завдання шкоди росту та розвитку рослин пшениці озимої. Удосконалено заходи контролювання бур'янових рослин, шкідників і захворювань у посівах провідної зернової продовольчої культури з урахуванням здатності її посівів створювати чітко виражене затінення поверхні ґрунту. Удосконалено економічну й енергетичну оцінку вирощування пшениці озимої після непарових попередників. The dissertation provides a theoretical generalization, presents a new theoretical justification and solution of the scientific problem of winter wheat crops protection from the weeds, pests and diseases in the northern steppe of Ukraine, based on which the effective tank mixtures of the herbicides, insectoherbicides and insectofungicides were developed. The results of the study including the evaluation of technical, economic and energy efficiency of the tank mixtures of pesticides are presented in the dissertation. Sowing of winter wheat after the non-fallow predecessors (maize for silage, alfalfa, sunflower, vetch-oats) created a different projective cover of the soil surface (from 50% to 84% – insufficient; from 85% to 95% – satisfactory; 96% or more – optimal). Crops with the insufficient projective cover had a higher contamination with weed seedlings and needed priority protection from them, especially from the most harmful annual and perennial rhizomic weed plants that penetrated the middle ("M") and upper ("U") tiers of the wheat stalks. With the optimal projective cover, effective biological control of most weeds was ensured until the harvest of winter wheat grain. The maximum technical efficiency (96.7%) in the winter wheat crops against roofing bromus (Bromus inermis Leyss.) was provided by a tank mix of the herbicides esterone + puma super (0.8 l / ha). To control the quarantine allergenic weed species common ragweed (Ambrosia artemisiifolia L.) it is most appropriate to use a tank mixture of the herbicides esterone + puma super (0.8 l / ha), which provides maximum technical efficiency of the pesticides – 94.0%. Maximum control of field bindweed (Convolvulus arvensis L.) provides a tank mixture of the herbicide monitor at a dose of 26 g / ha in combination with the adhesive surfactant trend (0.3 l / ha). Control of field bindweed is complicated by the appearance of its seedlings in winter wheat crops after the application of herbicides, which leads to additional use of the pesticides. Application of the tank mixtures of herbicide esterone (0.8 l / ha) and insecticide nurel D (0.75 l / ha), or the herbicides esterone (0.8 l / ha) and puma super (0.8 l / ha) + nurel D (0.75 l / ha), as well as esterone (0.8 l / ha) + plant growth regulator oxycarbam (150 g / ha) + nurel D (0.75 l / ha), provides almost complete destruction of all the existing pests: imago of sunn pest (Eurigaster integriceps), corn ground beetle (Zabrus tenebrioides), oscinella (Oscinella frit), winter moth (Operophtera brumata), and the larvae of cereal leaf beetle (O. melanopus) until the harvest of winter wheat grain. Complete control of the diseases up to the harvest of winter wheat is provided by the herbicidal-fungicidal tank mixtures of herbicide esterone (0.8 l / ha) + fungicide falcon (0.6 l / ha), and esterone (0.8 l / ha) + puma super (0.8 l / ha) + falcon (0.6 l / ha). With such treatment, almost 100% absence of the most common diseases of the winter wheat was noted. Almost full technical efficiency of the disease control (brown rust, fusarium wilt, septoria, helminthiasporiosis and powdery mildew) is provided in the fields with the application of mixtures containing herbicide starane premium (0.5 l / ha) + falcon (0.6 l / ha); monitor (26 g / ha) + falcon (0.6 l / ha) or monitor (20 g / ha) + esterone (0.6 l / ha) + falcon (0.6 l / ha). 25 days after the application of appropriate plant protection pesticides, the development of fusarium wilt reached 0.5%, septoria – 1%, and helminthosporiosis – 0.3%. At the same time, in the crops treated with herbicides peak (20 g / ha) and musket (20 g / ha) in combination with insecticide falcon (0.6 l / ha), it was not possible to control the development of diseases at all. Replacement of shelf plowing in the technology of growing winter wheat for the shallow flat-disk cultivation changes the distribution of weed seeds in the soil by concentrating most of it (85 – 90% of total) in the upper (0 – 0 cm) layer of the soil. At the same time, with the use of shelf plowing, weed seeds, on the contrary, were wrapped in the deeper soil layers along the tillage profile. The maximum grain yield of the winter wheat (3.59 t / ha) was provided by shelf-less tillage to a depth of 14–16 cm in combination with the use of mineral fertilizers at a dose of N30P30K30. The application of shallow disc tillage to a depth of 10–12 cm on the soil with the same fertilization level reduced the grain yield to 3.45 t / ha, which was 0.14 t / ha (or 4.0%) less. Similar patterns were also observed in the unfertilized fields. The use of herbicides in the winter wheat crops significantly increased the protein content of flour (compared to the control option without the herbicides). The maximum indicators of grain quality (the protein content 1.97 g / kg) were obtained in the fields where the herbicide banvel 4s was applied at a dose of 0.3 l / ha, and in the variant of the herbicide mastak (0.5 l / ha) application – the protein content 1.65 g / kg. On average, when using herbicides, the protein content in the winter wheat grain increased by 0.3 g / kg (by 25.4%) compared to the control, containing a minimum protein content in flour – 0.88 g / ha.
Scientifically substantiated concept of the control entomophytopathogenic complex in the winter wheat crops of the northern steppe of Ukraine
Keywords: якість зерна; grain quality; гербіциди; herbicides; пестициди; pesticides; бакова суміш; tank mix; пшениця озима; winter wheat; попередники; precursors; бур’яни; weeds; урожайність; yield; продуктивність; productivity